Legal Considerations of The Judges In Narcotics Rehabilitation Decisions (Analysis of Decisions Number: 112 / Pid.Sus / 2018 / PN.Pwt.) - Erik Harun Alrosid (UMPurwokerto Law Review, 2020)
Abstract A judge's legal considerations are essential in determining the value of a judge's decision that contains justice (ex aequo et bono), legal certainty, and benefits for the parties concerned. This study analyzes judges' legal provisions in verifying rehabilitation sentences for narcotics abuse cases and judges' legal considerations in rehabilitation decisions in narcotics cases Number: 112 / Pid.Sus / 2018 / Purwokerto District Court. The research method used in this research is a normative juridical approach, which is carried out through a literature study that examines secondary data in the form of laws and regulations and other legal documents and research results, assessment results, and other references. Legal considerations of Purwokerto District Court judges in examining and deciding cases of narcotics cases with case Number: 112 / Pid. Sus / 2018 / Purwokerto District Court by imposing a sentence without imprisonment, which is only in medical rehabilitation for 6 (six) months in the Mental Health Service Installation. The integrated Banyumas Regional Hospital is not correct. Judges need to consider imprisonment to give a deterrent effect to the accused himself and also to other people or the community from committing the same act. That was because when the medical examination was carried out at the Mental Health Service office of the Banyumas Regional General Hospital, based on the results of the examination, there were no significant physical and psychological symptoms of dependence on the defendant. Judges in giving judges consideration should be treated more carefully, well, and carefully.Keywords:   Legal considerations, Judges, RehabilitationAbstrakPertimbangan hukum hakim merupakan salah satu aspek terpenting dalam menentukan terwujudnya nilai dari putusan hakim yang mengandung keadilan (ex aequo et bono), kepastian hukum, dan manfaat bagi para pihak yang bersangkutan. Penelitian ini menganalisis terkait ketentuan hukum yang digunakan hakim dalam menjatuhkan vonis rehabilitasi terhadap kasus penyalahgunaan narkotika dan pertimbangan hukum hakim dalam putusan rehabilitasi dalam kasus narkotika Nomor: 112/Pid.Sus/2018/Pengadilan Negeri Purwokerto. Metode penelitian yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif yaitu dilakukan melalui studi pustaka yang menelaah data sekunder berupa Peraturan Perundang-undangan dan dokumen hukum lainnya, serta hasil penelitian, hasil pengkajian, serta referensi lainnya. Pertimbangan hukum hakim Pengadilan Negeri Purwokerto dalam memeriksa dan memutus perkara kasus narkotika dengan perkara Nomor: 112/Pid.Sus/2018/Pengadilan Negeri Purwokerto dengan menjatuhkan pidana tanpa penjara, yaitu hanya berupa rehabilitasi medis selama 6 (enam) bulan di Instalasi Pelayanan Kesehatan Jiwa Terpadu RSUD Banyumas tidak tepat. Hakim perlu mempertimbangkan pidana penjara untuk memberikan efek jera kepada terdakwa itu sendiri dan juga kepada orang lain ataupun masyarakat agar tidak melakukan perbuatan yang sama. Hal ini dikarenakan pada waktu dilakukan pemeriksaan medis di kantor Pelayanan Kesehatan Jiwa Rumah Sakit Umum Daerah Banyumas, berdasarkan hasil pemeriksaan tidak terdapat gejala ketergantungan Fisik dan Psikologis yang bermakna bagi diri Terdakwa. Hakim dalam memberikan Pertimbangan hakim seharusnya lebih disikapi dengan teliti, baik, dan cermat.Kata kunci:  Pertimbangan hukum,  Hakim, Rehabilitasi.